THE MODEL OF GEORGIAN ECONOMIC DEVELOPMENT AND POST CRISES GLOBAL ECONOMY (Globalization and Business, 2018)
Despite the fact that Georgia has already been an inde- pendent country for 25 years and inculcates the principles of market economy, the issue of choosing the model of country’s economic development has not been resolved up to the pres- ent time. Georgia frequently chooses radical models not only at the theoretical level, but also at the political one and has ambitions of merging them by unique prescription. Unfortu- nately, frequently there are attempts to borrow ideologically inappropriate models without comprehending their essence that causes problems for maintaining achieved successes.In order to choose a correct model, it is imperative to analyse at least at the theoretical level all those threats and possible successes that can be caused by choosing this or that model and its implementation. It is important that the society achieve consensus on what political philosophy the Georgian state system should be based on, the organic or mechanical theories of state.According to the first one the state is a natural organism, each individual is a part of this organism, and the state itself is a heart of this organism. According to this ideology; the individual is important as a part of society and his/her well- being should be considered in the context of the well-being of society.As regards the mechanical theory, it is based on the notion that the state is not an organic part of society and humans devised it to achieve their own goals.The economic essence of the noted theories is clearly reflected in Adam Smith and John Maynard Keynes’s theoreti- cal legacy. Smith was convinced that, if there are free markets and individuals act by their own interests, the whole economy works well. Smith claimed, that in the conditions of market economy the useful action of individuals’ own interests by the principle of “invisible hand” brings about maximization of the general well-being of society. According to Keynes, Smith’s “invisible hand” showed an utter irrelevance to the real devel- opments that became a reason for formulating a new macro- economic theory.Today our aim is to find that theoretical golden mean, which in case of its implementation, will enable Georgian eco- nomic model to be maximally effective and fair.